2007
DOI: 10.1007/s11926-007-0033-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of complement in antiphospholipid antibody-mediated thrombosis

Abstract: The mechanisms by which an antibody that reacts with phospholipids (universal components of mammalian membranes) causes thrombosis are not immediately obvious. The development of an animal model of antiphospholipid antibody syndrome has moved the field forward in dissecting the pathogenesis of antiphospholipid antibody syndrome and has implicated the complement system in the mechanism of disease. Understanding complement's role in promoting thrombosis will be important in designing safer, more effective approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…There is no convincing data that could explain a primary high level of DAF and MCP in the placentas of women with inherited thrombophilia, where the inflammatory reaction mediator is likely the thrombin [10,19]. LMWH mechanism of action known from APS related thrombophilia is not applicable there.…”
Section: Discussionmentioning
confidence: 99%
“…There is no convincing data that could explain a primary high level of DAF and MCP in the placentas of women with inherited thrombophilia, where the inflammatory reaction mediator is likely the thrombin [10,19]. LMWH mechanism of action known from APS related thrombophilia is not applicable there.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that binding of aPL to endothelial cells induces their activation, expressed by upregulation of adhesion molecules and cytokines, as well as their procoagulant state expressed by upregulation of tissue factor [78]. In addition, recent studies have provided evidence that activation of complement cascade by pathogenic aPL has an important role in endothelial cell injury and aPL-associated thrombosis [79]. Other mechanisms more directly related to thrombosis, probably frequently overlapping, such as interference of aPL with coagulation cascade, as well as activation of thrombocytes, have been proposed to be also involved in APS [80].…”
Section: Pathology and Pathomorphogenesismentioning
confidence: 99%
“…Inflammation can also cause endothelial damage. Evidence is accumulating that complement activation-which, like the thrombosis system, is also a cascade of tightly-controlled serine proteases-is required for thrombosis due to aPL [20][21][22][23]. Thus, two of Virchow's principles are met, and disturbance of blood flow is very common in everyday life.…”
Section: Antiphospholipid Antibodies and Thrombogenesismentioning
confidence: 99%